MAKNA SIMBOLIK TRADISI PERAHU BAGANDUANG SEBAGAI KEARIFAN LOKAL DI LUBUK JAMBI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - Gusra Rianti; Noor Efni Salam (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
Local culture is a culture that reflects from the cultural life of thecommunity from which it originated and became the pride of the area that has theculture. Each region has a diverse culture and has its own characteristics, as wellas Kuantan Singingi precise depths namely Jambi has local cultural traditionsperahu baganduang, in which there are symbols that symbolize the lives ofindigenous people in their daily jambi bottom, and also the value of local valuesthat must be preserved and introduced to the public, this phenomenon makes theresearcher is interested in conducting research in order to determine the symbolicmeaning contained in perahu baganduang tradition and values of local wisdomcontained therein.This research uses descriptive qualitative research methods and datacollection techniques using observation, interviews, documentation. Informants inthis study traditional leaders, and community and ninik mamak. The informantsobtained by purposive sampling technique. This technique determines theinformant deliberately and known in advance.The results of this study the researcher to get the meaning of the symbolicartifacts contained in perahu baganduang tradition that symbolizes the meaningof people's daily lives depths of Lubuk Jambi and obtained values of local wisdomin it reflects the behavior of the people in theLubuk Jambi live everyday life.Keywords: Perahu baganduang, symbols, tradition, local wisdom